Dominica : Staff Report for the 2011 Article IV consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Dominica has made significant progress over the past decade in strengthening its macroeconomic policy management. The 2011 Article IV Consultation report concludes that Dominica is emerging from the crisis. Growth turned positive in 2010, but tepid demand and the needed fiscal consolidation will weigh on the near-term prospects. Executive Directors endorse that fiscal policies need to be returned to a sounder footing to correct the weakening fiscal position. Given weakening revenues, IMF staff believes that achieving the authorities' target will necessitate additional fiscal measures beyond those envisaged in the budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet